FONEM SEGMENTAL DAN DISTRIBUSINYA DALAM BAHASA REJANG DIALEK MUSI - Sarwo F. Wibowo (Madah: Jurnal Bahasa dan Sastra, 2016)
This paper discuss about segmental phonemes in Rejang Musi Dialect. The interviewees are four native speaker of Rejang Musi dialect in Rejanglebong region. Primary data was collected from the population by using interview techniques with listening method. The collected data transcripted used phonetic alphabet, analized by minimal pair, data grouping, and data cultivation to found alophone. To make vowels map and consonant map was done observation on shape of mouth and tongue position. This research report that 26 segmental phonemes exist in Rejang Musi Dialect. The 26 phonemes is consist of seven vowels, that is /i/, /u/, /e/, /Ɛ/, /Ə/, /o/, and /a/, and 19 consonant, that is p/, /b/, /t/,/d/, /k/, /g/, /ŋ/, /?/, /s/, /h/, /c/, /j/, /l/, /m/, /n/, /ň/, /w/, /r/, and /y/.